1998
DOI: 10.1161/01.cir.98.22.2396
|View full text |Cite
|
Sign up to set email alerts
|

Human Prostaglandin Transporter Gene ( hPGT ) is Regulated by Fluid Mechanical Stimuli in Cultured Endothelial Cells and Expressed in Vascular Endothelium in Vivo

Abstract: Background-biomechanical forces generated by blood flow within the cardiovascular system have been proposed as important modulators of regional endothelial phenotype and function. This process is thought to involve the regulation of vascular gene expression by physiological fluid mechanical stimuli such as fluid shear stresses. Methods and Results-We demonstrate sustained upregulation of a recently identified gene encoding a human prostaglandin transporter (hPGT) in cultured human vascular endothelium exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
36
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 23 publications
4
36
2
Order By: Relevance
“…Topper et al (34) reported that antisera against the COOH terminus of human PGT labeled endothelia, but not other structures, in the human kidney, results which vary from the present data. In addition to recognizing PGT in endothelia, our anti-rat mAb20 also recognizes immunoreactivity in glomerular mesangial cells, arteriolar muscularis layers, collecting ducts, medullary interstitial cells, and papillary surface epithelia.…”
Section: Discussioncontrasting
confidence: 99%
“…Topper et al (34) reported that antisera against the COOH terminus of human PGT labeled endothelia, but not other structures, in the human kidney, results which vary from the present data. In addition to recognizing PGT in endothelia, our anti-rat mAb20 also recognizes immunoreactivity in glomerular mesangial cells, arteriolar muscularis layers, collecting ducts, medullary interstitial cells, and papillary surface epithelia.…”
Section: Discussioncontrasting
confidence: 99%
“…The reported increased PGI2 bioavailability in response to flow might very well be accomplished by the highly increased expression of the KLF2-induced prostaglandin transporter SLCO2A1, which itself was previously shown to be highly responsive to shear stress. 36 Collectively, the presented data lead to the novel insight that KLF2 gene regulation is almost entirely dedicated to the control of many of the genes that define the key functions of the normal functioning endothelium of the completely developed healthy arterial tree. The large number of downstream transcriptional targets of KLF2 (Table 2) precludes a simple direct transcription factor-to-function relation.…”
Section: Discussionmentioning
confidence: 97%
“…One study showed that PGE 2 transport was inhibited in the rabbit uvea by topical application of LPS (2), whereas another study failed to detect any effect of IL-1␤ on PGT expression in human endothelial cells in vitro (64). Administration of IL-1␤ or TNF-␣ in vitro (37,46) and shock-inducing doses of LPS in vivo (6,23,39) were shown to inhibit the catabolism of PGE 1 and PGE 2 and expression of 15-PGDH.…”
mentioning
confidence: 99%